Circulating Tumour Cells (CTCs) in NSCLC: From Prognosis to Therapy Design - Zdeněk Kejík; Robert Kaplánek; Petr Dytrych; Michal Masařík; Kateřina Veselá; Nikita Abramenko; David Hoskovec; Martina Vašáková; Jarmila Králová; Pavel Martásek; Milan Jakubek (MDPI AG, 2021)
Designing optimal (neo)adjuvant therapy is a crucial aspect of the treatment of non-small-cell lung carcinoma (NSCLC). Standard methods of chemotherapy, radiotherapy, and immunotherapy represent effective strategies for treatment. However, in some cases with high metastatic activity and high levels of circulating tumour cells (CTCs), the efficacy of standard treatment methods is insufficient and results in treatment failure and reduced patient survival. CTCs are seen not only as an isolated phenomenon but also a key inherent part of the formation of metastasis and a key factor in cancer death. This review discusses the impact of NSCLC therapy strategies based on a meta-analysis of clinical studies. In addition, possible therapeutic strategies for repression when standard methods fail, such as the administration of low-toxicity natural anticancer agents targeting these phenomena (curcumin and flavonoids), are also discussed. These strategies are presented in the context of key mechanisms of tumour biology with a strong influence on CTC spread and metastasis (mechanisms related to tumour-associated and -infiltrating cells, epithelial-mesenchymal transition, and migration of cancer cells).